Accountability and Transparency in Managing Village Funds in Ngawen, Blora, Central Java - Windyastuti, Windyastuti; Fitriyani, Lita Yulita; Marita, Marita; Afifah, Mufida Nur (Proceeding UII-ICABE, 2020)
This research was conducted to determine the effect of accountability and transparency in managing of village allocation funds in Ngawen District, Blora Regency. This study uses a quantitative approach with regression analysis as a tool. The influence of accountability and transparency can identified from the performance of the Ngawen district government in the presentation of information and comparative reports on village fund allocation with the previous year. The result shows that accountability and transparency had an influence on the management of village fund allocation, especially in the Ngawen District of Blora Regency. The higher the accountability of the Ngawen District government, the better the management of village fund allocation would be. Moreover, in the transparency dimension, it is showed that a better transparency of the Ngawen District government will improve the management of village fund allocation. Keywords: accountability, transparency, managing, village funds